PROSPECTS FOR THE DEVELOPMENT OF FAMILY MEDIATION IN RUSSIA AND THE REPUBLIC OF KAZAKHSTAN - Kurmaeva , Natalia; Usmanova, Elena; Khudoikina, Tatyana (Scientific Journal of Pedagogy and Economics, 2021)
the relevance of the topic is due to the fact that the use of mediation in resolving family disputes is currently getting more and more demanded form of conflict resolution. The purpose of the article is to study and analyze the features of the legal regulation of family mediation in Russia and Kazakhstan, as well as to identify promising directions for the development of this institution. Conclusions are drawn about the need to improve the legislation governing family mediation. Taking into account the cultural and national characteristics of states, it is necessary to include them in the process of organizing mediation services, the creation of state reconciliation services for family matters, while it is desirable to include in their work not only lawyers, but also psychologists and teachers who know mediation technologies. Attention is drawn to the fact that the formation of a corps of professional family mediators and the creation of an association of family mediators would be an effective element in the development of optimal mechanisms for coordinating mediation with jurisdictional procedures. The possibility of legislative consolidation of the obligation of pre-trial appeal to a mediator to resolve a family legal dispute was revealed. This proposal will significantly reduce the number of cases of divorce and reduce the court burden.